2016
DOI: 10.25011/cim.v39i6.27513
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between internet addiction and alexithymia among university students

Abstract: Purpose: Epidemiological studies concerning internet addiction found that 50% of internet addicts also have other kinds of psychiatric disorders. This study aims to examine the relationship between alexithymia and internet addiction levels among Turgut Özal University students in Ankara, Turkey. Method: University students (1,107 students; 452 students from 12 associate degree programs and 655 students from 10 undergraduate programs) participated in the study. The researchers used the personal information for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 16 publications
(32 reference statements)
1
14
2
Order By: Relevance
“…In problematic internet/gaming several studies have explored and highlighted to role of alexithymia and its links with other therapeutic issues. For instance, it has been shown that alexithymic individuals are more associated with Internet addiction than non-alexthymic ones (Baysan-Arslan et al, 2016). In this research, the authors consider that the difficulty in identifying and differentiating emotions that characterizes alexithymia may lead individuals with this affliction to regulate their emotional states via their addictive activities.…”
Section: Therapeutic Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In problematic internet/gaming several studies have explored and highlighted to role of alexithymia and its links with other therapeutic issues. For instance, it has been shown that alexithymic individuals are more associated with Internet addiction than non-alexthymic ones (Baysan-Arslan et al, 2016). In this research, the authors consider that the difficulty in identifying and differentiating emotions that characterizes alexithymia may lead individuals with this affliction to regulate their emotional states via their addictive activities.…”
Section: Therapeutic Implicationsmentioning
confidence: 99%
“…Considering the possible association between alexithymia and problematic gaming as a manner to regulate emotions (Baysan-Arslan et al, 2016;Bonnaire and Baptista, 2019), the Emotion Regulation Therapy (ERT) might strengthen the therapeutic process. The aim being that the observed difficulties in Internet (including VG) addicts to identifying emotions and regulating affects in Craparo, 2011) could be, at least partially, overcome through the ERT process.…”
Section: Therapeutic Implicationsmentioning
confidence: 99%
“…Similarly, Katsifaraki and Tucker in their study in the UK; 8.7% of the nursing students were alexithymic. The prevalence of alexithymia in studies conducted with Turkish university students was between 3% and 12% . In studies conducted with university students in different countries, various alexithymia rates have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of alexithymia in studies conducted with Turkish university students was between 3% and 12%. [24][25][26] In studies conducted with university students in different countries, various alexithymia rates have been reported. For example, in a study of alexithymia, prevalence in the USA was 5.6%, 27 10 % in Canada, 28 10% in Italy, 30 17.92%…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation